2023
DOI: 10.1021/acsbiomaterials.2c01553
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Serum Albumin: From Structure and Biological Properties to Functional Biomaterials for Bone Repair

Abstract: Serum albumin (SA), one of the most abundant proteins in blood plasma, plays essential roles in all living processes and has been used in various biomedical applications. Biomaterials fabricated from SAs (human SA, bovine SA, and ovalbumin) exhibit proper microstructure and hydrophilicity as well as remarkable biocompatibility; this makes them ideal for use in bone regeneration. This review provides a comprehensive overview of the structure, physicochemical properties, and biological features of SAs. SAs can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 133 publications
0
0
0
Order By: Relevance
“…Serum albumin (SA), with a molecular weight of 66.5 kDa, is the most abundant protein found in the bloodstream 115 . It possesses a remarkable systemic circulation time of approximately 19 days 116 .…”
Section: Cell/protein Choices For In Vivo Hitchhikingmentioning
confidence: 99%
“…Serum albumin (SA), with a molecular weight of 66.5 kDa, is the most abundant protein found in the bloodstream 115 . It possesses a remarkable systemic circulation time of approximately 19 days 116 .…”
Section: Cell/protein Choices For In Vivo Hitchhikingmentioning
confidence: 99%
“…According to previous studies, albumin is successfully used as a biostatic structure, biomaterial coating, or highly biocompatible scaffold [32,33,[40][41][42][43]. Tissue-engineered serum albumin hydrogels used as scaffolds offer a porous structure to achieve great fluid permeability and effective nutrition flow to provide better tissue regeneration [44]. Such scaffolds could be utilized in numerous clinical applications that require grafting materials that promote superior healing processes [45].…”
Section: Introductionmentioning
confidence: 99%
“…Such scaffolds could be utilized in numerous clinical applications that require grafting materials that promote superior healing processes [45]. Furthermore, albumin is an active molecule; the mode of action is not yet fully clarified, but previous animal and in vitro studies have shown that after bone fractures, the local albumin concentration increases [44,46]. Even twelve months after albumin-coated bone allograft implantations, intensive osteoblast action can be observed [47].…”
Section: Introductionmentioning
confidence: 99%